Global linkages among energy, food and water: an economic assessment - Ringler, Claudia; Willenbockel, Dirk; Pérez, Nicostrato D.; Rosegrant, Mark W.; Zhu, Tingju; Matthews, Nathaniel (Springer, 2016)
The resolution adopted by the General Assembly of the United Nations on 25 September 2015 is symptomatic of the water-energy-food (WEF) nexus. It postulates goals and related targets for 2030 that include (1) End hunger, achieve food security and improved nutrition, and promote sustainable agriculture (SDG2); (2) Ensure availability and sustainable management of water and sanitation for all (SDG6); and (3) Ensure access to affordable, reliable, sustainable, and modern energy for all (SDG7). There will be tradeoffs between achieving these goals particularly in the wake of changing consumption patterns and rising demands from a growing population expected to reach more than nine billion by 2050. This paper uses global economic analysis tools to assess the impacts of long-term changes in fossil fuel prices, for example, as a result of a carbon tax under the UNFCCC or in response to new, large findings of fossil energy sources, on water and food outcomes. We find that a fossil fuel tax would not adversely affect food security and could be a boon to global food security if it reduces adverse climate change impacts.